Pendampingan Penerapan Akuntansi Keuangan untuk Meningkatkan Transparansi dan Akuntabilitas Pengelolaan Dana Anggota pada Koperasi Kredit Kosayu - Dwi Anggarani; Indah Dewi Nurhayati; Irfan Fatoni; Nasharuddin Mas; Vidya Wulandari (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
The Kosayu Credit Union is a savings and loan cooperative that plays a role in professionally collecting and managing its members’ funds. As demands for transparency and accountability increase, the cooperative’s management needs to have a sufficient understanding of the application of financial accounting and the use of information technology in financial recording and reporting processes. This community service activity aims to provide guidance on the implementation of financial accounting to improve the quality of member fund management at Kosayu Credit Union. The implementation methods include observation, problem identification, technical guidance, hands-on practice, and evaluation of activity results. The guidance covered financial data management, analysis and calculation of Income Tax Article 21 using Microsoft Excel, inventory coding, data archiving, and optimization of the Credit Union System Online (CUSO) application. The results of the activity showed an increase in the managers’ understanding of transaction recording processes, inventory management, data archiving, and the preparation of more systematic financial reports. Furthermore, more optimal use of information technology supports the presentation of financial information that is accurate, timely, and accountable. This mentoring program has made a positive contribution to enhancing transparency and accountability in the management of member funds, thereby supporting the realization of sound cooperative governance.